PTH-116 Evaluation of the d'amico clinical staging system and the albi grade for prognostication in cirrhosis and hepatocellular carcinoma. (22nd June 2015) - Kia, R; Buck, I; Clark, K; Halpen, A; Farrell, C; Palmer, D; Cross, TJS
Abstract : Introduction: The ability to prognosticate in both cirrhosis and hepatocellular carcinoma (HCC) is vital for correct treatment decisions. For HCC, many staging systems incorporate tumour characteristics but inadequately consider underlying liver dysfunction. Therefore, models that accurately stratify the degree of liver dysfunction, may improve our understanding of its impact on survival in patients with HCC. We aimed to compare current and potential prognostication models of survival for patients with cirrhosis, and to determine their applicability in HCC patients. Method: A single-centre retrospective comparative analysis of cohorts of consecutive patients diagnosed with cirrhosis alone was performed against HCC patients with background cirrhosis. The Child-Pugh score, MELD score, UKELD score, the D'Amico clinical stage of cirrhosis (D'Amico G, et al ., J Hepatol, 2006) and the Albumin-Bilirubin (ALBI) grade – a composite model of liver function using serum bilirubin and albumin levels (Johnson PJ, et al ., J Clin Oncol, 2015), were determined at diagnosis. The patient outcome at 1 year post diagnosis was also determined. The primary outcome was the models' ability to predict death at 1 year. The impact of liver dysfunction on survival in patients with HCC was also evaluated. Results: A total of 117 patients were included in this study (67% male, median age: 57 years). The aetiologies were ALD (52%), NASH (15%), HCV (11%), PBC (5%), HBV (2%), AIH (2%), mixed aetiology (9%) and others (5%). 75% of patients had cirrhosis alone while 25% had HCC. All the evaluated models accurately predicted death at 1 year (all with p < 0.001). The risk of death was greater amongst patients with HCC (p = 0.04; OR 2.6, 95% CI: 1.1–6.3) compared to patients with cirrhosis alone, despite favourable levels of albumin (37 vs. 35 g/L, p = 0.003), bilirubin (25 vs. 87 μmol/L, p < 0.0001) and prothrombin time (12 vs. 16 s, p < 0.0001). D'Amico stage 3–4 also predicted a significantly increased risk of death for cirrhotic patients (p < 0.0001; OR 5.7, CI: 2.4–14). Conclusion: All the evaluated prognostication models performed well, though the study was limited by a small cohort of patients with HCC. Despite a better liver function, the survival of patients with HCC was inferior, suggesting that tumour biology has a greater impact overall compared to the degree of underlying liver dysfunction. However, future studies specifically looking at the impact of liver dysfunction on survival in non-surgical treatment of HCC should be considered. Disclosure of interest: None Declared.